The relationship between economic status and readiness for marriage and pregnancy in PEKKA in Kamal Village, Arjasa District, Jember Regency - Pripuspitasari, Dini Eka; Fitrianingtyas, Rizki (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The family is the smallest unit of social groups found in the social order in which there is a process of adjustment in making appropriate decisions to reach a collective agreement. In practice, household life does not always run harmoniously. When a woman faces a divorce situation, there will be several impacts on her reproductive health in the future due to the situation that she is currently in a vulnerable group. The vulnerable situation in question is related to the potential for changing sexual partners, the potential for violence due to the various conflicts they face, the potential for sexual harassment in connection with society's stereotypes in viewing widow status. This research aims to find out how the social and economic status of women heads of households will influence their decisions in determining their readiness to marry and become pregnant again. With the aim of empowering women's abilities to overcome this situation, women heads of families must be encouraged to adopt adaptation patterns to improve social conditions and increase income to meet their needs. These adaptation patterns include being active in village activities, being an entrepreneur and working as a laborer, so that later this will also have an impact on his mindset regarding the decision to remarry. By implementing this adaptation pattern, it is hoped that the quality of life of female heads of households will become better and more independent. When she decides to remarry, meaning she is ready to get pregnant again, a woman must also be empowered to be able to recognize and assess her readiness comprehensively to prevent a recurrence of divorce like her previous marriage. In this way, all reproductive health risks that exist with the PEKKA situation will also be anticipated, so that PEKKA women will be able to achieve optimal reproductive